M.A.M.A.A.M Enterprise : Herbal Soap / Muhammad Amir Kamaruddin ...[et al.] - Kamaruddin, Muhammad Amir; Masahor, Ahmad Tajuddin; Bakar, Muhammad Siddiq; Mohd Najihan, Ahmad Arif Hakimi; Awg Taib, Awang Mohd Noor Hamin; Alharsikanill, Mukhlis (2017)
Our target market is to sell the herbal soap product to the customer especially to the local market in Sarawak. They have been identified as people with needs or wants that can be met with the products from our company.